Good Practices in Educating and Informing the New Generation of Consumers on Organic Foodstuffs - Lelia Voinea; Dorin Vicenţiu Popescu; Mihai Teodor Negrea (Amfiteatru Economic Journal, 2015)
The positive image of organic products among consumers has grown gradually. Today, this image is based on a number of researches and studies conducted by specialized government bodies and private organizations and research institutes that show that these products offer, in terms of their nutritional profile, a high intake of nutrients with positive impact on health. Consumers also know that operators who produce and sell such products are subject to rigorous regulations for obtaining the organic certificate and the right to use the organic logo and are regularly monitored by inspection and certification bodies in this regard – facts that increase the new generation of consumers' confidence in the quality and safety of these products. Having the aim of highlighting the decisive factors which contribute to the creation of a positive image for the ecological foodstuff among consumers and in order to understand the real motivations of the decisional process of buying these products, an exploring marketing research was realized among the new generation of consumers. Another aim of the investigation is the identification of some problems connected with a possible unbalanced nutritional profile of some ecological products commercialized in Romania and whose consumption may be inadequate for a diet and, implicitly, for some consumers' health, especially for those having certain food restrictions caused by nutritional diseases from which they suffer. In this regard, we are going to analyse, from a scientific point of view, the nutritional profile of some ecological foodstuff found on the market in Romania, using an accredited and standardized method within the European Union- the SAIN-LIM method. Thereby, the paper aims to highlight the antithesis between the formal positive consumer perception and the nutritional profile of some organic products on the Romanian market. Through this endeavour we intend to draw attention on the need of adopting a good practices guideline in education and consumer information in order to acquire the skills for a more correct buying decision. We believe that these good practices should be included among the pursuits of the education system, government structures and specialized NGOs.
Keywords: M10; O13; Z10; 330; the new generation of consumers; ecologic foodstuff; good practices; nutritional profile; consumer perception; education and consumer information